2017
DOI: 10.1136/bcr-2016-216267
|View full text |Cite
|
Sign up to set email alerts
|

Cystic lymphangioma of spleen in adults

Abstract: Splenic diseases are rare. Tumours of the spleen are classified as either benign or malignant. Primary benign tumours of the spleen are extremely rare, identified on surgery and autopsy, accounting for <0.007% of all splenic tumours. Splenic lymphangiomas are benign cystic tumours resulting from congenital malformations of the lymphatic system that appear as a single or multiple lesions of the spleen. It mainly affects children and is rarely manifested after the age of 20 years of age. We report a case of cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…30 This was clinically diagnosed as a hydatid cyst which is a common radiological differential diagnosis for a cystic lesion in the spleen. 31 One spleen which was resected in view of a parenchymal space occupying lesion was revealed to have a hamartoma. The rarity of this lesion in this series is concordant with other studies which have shown hamartomas to be extremely uncommon lesions with an incidence of 0.024% to 0.13% in an autopsy review.…”
Section: Discussionmentioning
confidence: 99%
“…30 This was clinically diagnosed as a hydatid cyst which is a common radiological differential diagnosis for a cystic lesion in the spleen. 31 One spleen which was resected in view of a parenchymal space occupying lesion was revealed to have a hamartoma. The rarity of this lesion in this series is concordant with other studies which have shown hamartomas to be extremely uncommon lesions with an incidence of 0.024% to 0.13% in an autopsy review.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a large SL, the symptomatology may include left upper quadrant pain with splenomegaly, nausea, vomiting, loss of appetite, shortness of breath, abdominal distention, further generalized symptoms secondary to compression of adjacent viscera or an acute abdomen, as in our patient, in case of complications like as rupture or infection [ 2 ]. The differential diagnosis is broad including hemangioma, splenic infarction, pseudocyst, epidermoid cyst, mesothelial cyst, parasitic or hydatid cysts, septic embolism, old hematomas, lymphoma or metastasis [ 9 , 10 ]. Preoperative diagnosis is difficult like as for other pathologies [ 11 ], depending on the non specificity of symptoms and signs; however it’s improved by medical imaging including abdominal ultrasound (US), abdominal CT scan and magnetic resonance imaging (MRI) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, histological examination reveals flattened endothelial lining in cystic lymphangiomas, while epidermoid cysts display stratified squamous epithelial lining. Another remarkable factor differentiating splenic cystic lymphangiomas from splenic epidermoid cysts is that lymphangiomas present with dilation of the lymphatic vessels of the splenic parenchyma while no venous abnormalities are typically associated with splenic epidermoid cysts [11, 12].…”
Section: Discussionmentioning
confidence: 99%